Sexual Happiness in Marriage a Christian interpretation of sexual adjustment in marriage - Miles, Herbert Jackson (Grand Rapids Zondervan Publishing House, 1976)
In this frank, honest, discussion of the role of sex in marriage, Dr. Herbert J. Miles thoroughly and carefully examines attitudes and techniques essential to sexual compatibility. Those who read it and follow its suggestions will be able to analyze and correct sexual problems in their marriages.
Keywords: Sex in marriage. Sexual ethics. Marriage